AKIBAT KODE ETIK PROFESI AUDIT TERHADAP KUALITAS AUDIT AUDITOR INDEPENDEN (Studi pada KAP Malang) - Linda Wulandari; Moh. Amin; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study became performed to examine the effect of the standards of integrity, objectivity, competence and the concepts of professional behavior contained in the code of ethics of the general public accountant career at the fine of the audit of independent auditors. The difficulty of the look at is an impartial auditor running at KAP within the Malang location, with junior, senior, managerial and partnership positions. There have been records from sixty five respondents, which were then examined using numerous methods of linear regression evaluation, validity and reliability assessments, classical bet checks and hypothesis checking out. The effects of the SPSS 26 test for windows display that the precept of integrity and the principle of competence do no longer have a considerable effect on the excellent of the impartial auditor's audit, while the principle of objectivity and the precept of professional behavior have a big effect on the excellent of the independent auditor's audit.Keywords: Integrity. Objectivity, competence. Professionalism, nice of audit.